Identifying Social factors that Stratify Health Opportunities and Outcomes (ISSHOOs) in pain research: Consensus recommendations for the collection and reporting of equity-relevant data - Karran, E. L.; Cashin, A. G.; Chiarotto, A.; Sharma, S.; Barker, T.; Boyd, M. A.; Maxwell, L. J.; Mohabir, V.; Petkovic, J.; Tugwell, P.; Moseley, G. L.; Ajayi, O. K.; et al. (EClinicalMedicine, 2025)
Background The aspiration to improve health equity is fundamental to scholarly focus and action in public health, and highly relevant to addressing the global burden of pain–the leading contributor to disability worldwide. There is potential for advancement towards health equity to be facilitated by greater access to data that identifies the role of socio-demographic factors in pain and health outcomes. Methods The ‘Identifying Social factors that Stratify Health Opportunities and Outcomes (ISSHOOs) in Pain Research’ project was a multi-stage process that aimed to reach consensus on the most important equity-relevant items to include in all human adult pain research. Conducted April 2022–May 2025, it incorporated two scoping reviews (published 2023), an international Delphi study (published 2025), consensus meetings and focus groups; prioritising global participation, patient perspectives, and interdisciplinary expertise throughout. Findings Three hundred and four individuals from 45 countries, across six continents, contributed to developing two sets of items. Set A, the ‘minimum dataset’, is a globally relevant set of eight standardised socio-demographic items (age, sex, gender identity, place, race/ethnicity/cultural identity, education, financial position, work status), accompanied by concise guidance to assist implementation and setting-specific tailoring; Set B is an ‘extended dataset’ of optional items from which researchers can select items consistent with their study population and research questions. The ISSHOOs recommendations offer a culturally sensitive, cross-culturally relevant, practical and highly useful resource. Interpretation Routine adoption and clear reporting of the ISSHOOs datasets across all human adult pain research will lead to improved and harmonious descriptions of research participants across health equity domains. Our goal is to promote equity-relevant awareness and understanding, and ultimately drive progress towards reducing avoidable disparities in health for people with pain, with potential for broader application to other fields of health.